Perioperative Correction of Metabolism in Patients with Lung Cancer - A. Yu. Yakovlev; O. S. Gordeyeva; A. N. Denisenko; A. Yu. Vorontsov (Общая реаниматология, 2011)
Objective: to reveal the features of perioperative metabolic disturbances in patients with lung cancer after pulmonectomy and a possibility of their correction with perioperative «Standard» formula sipping and with postoperative intravenous cytoflavin. Subjects and methods. The paper presents the results of a prospective randomized study of the efficiency of correction of metabolic disturbances in patients with lung cancer with perioperative enteral «Standard» formula sipping (5 days before surgery and 12 days after surgery). The study was conducted in 326 men aged 36 to 68 years. Arterial blood metabolic parameters (glucose, lactate, and pyruvate) and daily urine urea were estimated. Results. There was an association of preoperative metabolic disturbances with body mass index (BMI). Inclusion of sipping into perioperative therapy did not exert a considerable impact on the cause of postoperative metabolic disturbances. Key words: lung cancer, pul-monectomy, body mass index, sipping, cytoflavin.